Effects of foliar application of urea and potassium chloride on some physicochemical properties of “Damson ”plum fruits - Aljabary, Ali Muhi Aldeen Omar (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was carried out on Damson Plum trees( Prunus domestica L.) selected from orchard during 2015 growing season in Brzinjah district, Sulaimani governorate, Iraqi Kurdistan Region, to investigate the effect of different level of urea (0, 0.5 and 1%), and potassium chloride (KCl) (0, 1and 2%) on some physicochemical properties of plum fruits. Trees were sprayed with Urea and potassium chloride at two different times, early May, and early June, 2015. The results shows that, spraying with 0.5% urea cased a significant decrement of moisture and pectin percentage of fruit and increased the dry matter and peroxidase enzyme activity, while the high level of urea (1%) decreased significantly fruit size, pulp/fruit percentage and pulp/seed percentage. The foliar spray with 2% of Potassium Chloride led to significant increase in the value of fruit size, fruit diameter, pulp/fruit percentage, and pulp/seed percentage, while significant decrease in peroxidase enzyme activity compared with control treatment. On the other hand, the Treatment combinations between spray of 0.5% urea and 2% KCl gave the highest means of fruit size, fruit length, fruit diameter, pulp/fruit percentage and pulp/seed percentage.
Keywords: Damson Plum; Potassium Chloride; Urea